Process of extraction and isolation of canthaxanthin from saline bacteria biomass Paracoccus carotinifaciens VTP20181 isolated in Vietnam - Anh, Dang Vet; Toan, Tran Quoc (Vietnam Journal of Marine Science and Technology, 2020)
Canthaxanthin is a natural carotenoid, which can be biosynthesized from several different bacterial strains and exhibits a wide range of biological benefits such as antioxidant, immune booster, and vascular stabilization. Canthaxanthin is widely used in the food and pharmaceutical industries as a natural colourant, and its production from natural sources has been the topic of growing interest. In this study, we established the process of extracting, enriching and isolating canthaxanthin from the post-fermentation biomass of the saline bacteria Paracoccus carotinifaciens VTP20181 isolated in Vietnam at laboratory scale. This process consists of 5 steps: Dry biomass generation, dry biomass extraction, removal of saturated fat, fast column chromatography and slow column chromatography, canthaxanthin purification. Canthaxanthin compound is obtained with 98% purity. Canthaxanthin extraction and purification efficiency of the whole process reached 55.5%.